Makna Denotatif,konotatif,dan mitos mahfudzat man jadda wa jada : analisis semiotika Roland Barthes - Adi Pandu Winata; Armasito Armasito (Yayasan Haiah Nusratul Islam, 2026)
The saying “Man jadda wa jadda” is often used in the Islamic education tradition and carries a moral message about diligence and success. This expression is frequently used, especially in the educational context, as a motivational principle for everyday life. This study aims to analyze the semantic meaning of the expression using Roland Barthes' semiotic approach. The research method employed is a descriptive qualitative approach with text analysis techniques. The analysis is conducted on several levels: surface meaning, associative meaning, and mythic (ideological) meaning. The findings indicate that at the surface level, the expression signifies a causal relationship between seriousness and success. On an associative level, the expression encompasses values such as diligence, optimism, and a sense of responsibility. On a mythic level, the expression constructs a meritocratic ideology that is dominant in society, where success is determined by individual effort.